2018
DOI: 10.1089/lgbt.2017.0091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Self-Reported Diabetes by Sexual Orientation: Results from the 2014 Behavioral Risk Factor Surveillance System

Abstract: Sexual minorities may be at increased risk for diabetes than their heterosexual peers. This may be due partly to the chronic stressors associated with being a member of a marginalized population. Future research should explore the underlying causes and consequences of LGB diabetes disparities and elucidate best practices to improve diabetes screening and care for these vulnerable patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…This was a consistent finding from numerous large US epidemiological studies that contributed to the meta-analysis but had no explanation as to why this is the case. In gay and bisexual men, there are apparently higher rates of diabetes mellitus compared to heterosexual men (Beach et al 2018). This study again found no difference in diabetes mellitus rates in lesbians and bisexual women compared to heterosexual women (Beach et al 2018).…”
Section: Cardiovascular Disease and Other Conditionssupporting
confidence: 45%
“…This was a consistent finding from numerous large US epidemiological studies that contributed to the meta-analysis but had no explanation as to why this is the case. In gay and bisexual men, there are apparently higher rates of diabetes mellitus compared to heterosexual men (Beach et al 2018). This study again found no difference in diabetes mellitus rates in lesbians and bisexual women compared to heterosexual women (Beach et al 2018).…”
Section: Cardiovascular Disease and Other Conditionssupporting
confidence: 45%
“…9 Higher rates of HIV and cancer in certain SGM subpopulations make them more likely to be immunocompromised and, therefore, vulnerable to infections compared with cisgender and heterosexual groups. 6,7,10 In addition, some SGM subgroups use tobacco and marijuana more frequently compared with cisgender, heterosexual peers, 11 and various SGM subgroups are more likely to have chronic conditions associated with COVID-19-related risks, including diabetes, 12 asthma, 13 and hypertension. 14 SGM people are less likely to seek health care due to stigma and discrimination, 15 and due to structural factors that make care financially inaccessible.…”
Section: Introductionmentioning
confidence: 99%
“…Within epidemiological studies, older age, greater BMI, and non‐White race have been shown to be the strongest risk factors for the development of diabetes . Increasingly, research has also demonstrated that sexual minorities may be at increased risk for the development of diabetes …”
Section: Introductionmentioning
confidence: 99%
“…11 Increasingly, research has also demonstrated that sexual minorities may be at increased risk for the development of diabetes. 12,13 In this study, we used a multiyear pooled dataset of high-school youth to articulate the prevalence of major diabetes risk factors identified by the ADA and within the epidemiologic scientific literature, including PA, SB, and BMI, and to identify significant differences in these risk factors based on sexual identity. Based on prior research, we hypothesized that, even after adjusting for other known diabetes risk factors, sexual minority youth would have greater behavioral risk factors for type 2 diabetes and be more likely to be overweight or obese than their sex-matched heterosexual counterparts.…”
mentioning
confidence: 99%